Phytochemical Screening of Strobilanthes crispa Leaf Extract Obtained by Ultrasound-Assisted Extraction (UAE) Method - Hasnaeni; Nurlina; Handayani, Selpida; Anasya, Andi Fara; Wenni, Asyam Hafidz (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The study was conducted to determine  of secondary metabolite compounds in the ethanol extract of keji beling leaves (Strobilanthes crispa (L.). Keji beling leaves are known to possess pharmacological effects such as antioxidant, antibacterial, and anticancer. These pharmacological effects are due to the presence of secondary metabolites. This study aims to investigate the secondary metabolite compounds contained in keji beling (S. crispa). Fresh keji beling leaves were dried, ground into powder, and extracted using 70% ethanol solvent using the Ultrasonic Assisted Extraction (UAE) method. Phytochemical screening was carried out by adding reagents specific for secondary metabolites. The test results showed that the ethanol extract of keji beling leaves contained positive flavonoids, alkaloids, saponins, and tannins, while the terpenoid test showed negative results. The presence of these metabolites indicates that keji beling leaves have the potential as a source of bioactive compounds and can be developed into raw materials for herbal medicine preparations.